A transparent UWB antenna with a 5 to 6 GHz band notch using two split ring resonators - Rani, Mohd. Subri Abdul (Applied Computational Electromagnetics Society (ACES), 2015)
A miniaturized thin film transparent ultrawideband (UWB) antenna design with a band notch is presented. A pair of split-ring resonators (SRRs) is placed besides the radiating element to realize the band notch centered at 5.5 GHz. The proposed transparent antenna covers the whole 3.1 to 10.6 GHz UWB frequency band with a notch from 5 to 6 GHz to isolate interferences from wireless local area network (WLAN) and dedicated short-range communication (DSRC) applications. The transparency of this antenna of up to 80% is enabled by the fabrication on a conductive silver coated thin film (AgHT-8). Hence, the proposed transparent antenna is a suitable for UWB home entertainment network (IEEE 1394 over UWB network) for green building applications, where high data rates are required for multimedia transfer. Implementation of the proposed transparent antenna will reduce the space consumption due to its very low thickness and low profile, while at the same time increasing the aesthetic values of the installed wireless system due to its high transparency.